Arabic manuscripts : a vademecum for readers - Gacek, Adam (Handbuch der Orientalistik. Nahe und der Mittlere Osten, 2009)
The main sequence is comprised of approximately 200 entries dealing with almost all aspects of Arabic manuscript studies (codicology and paleography); includes appendices covering abbreviations, letterforms, såurah-headings, major reference works, and a guide to the description of manuscripts, as well as charts of major historical periods and dynasties.